Utilizing End-of-Life Tyre Crumb Rubber in Cement Formulation by Substituting Sand with Different Volume Proportions - Kolendo Girts; Kuldasheva Aziza; Korjakins Aleksandrs; Sahmenko Genadijs; Bajare Diana (Environmental and Climate Technologies, 2023)
The number of end-of-life tyres recycled into crumb rubber varies widely across different countries and regions, depending on factors such as local regulations, infrastructure, and demand for the product. According to the International Rubber Study Group (IRSG), the global production of crumb rubber from end-of-life tires was estimated to be around 12.7 million metric tons. This study is devoted to the development of cement composites where the sand was partially and fully replaced with a specially prepared fine fraction of crumb rubber. Partial replacement of sand with crumb rubber changes the workability of the concrete. The lighter concrete composite may also have improved acoustic and thermal insulation properties. Complete substitution of sand with crumb rubber leads to a lighter concrete composite, featuring reduced densities and enhanced ductility. In these experiments, prisms of dimensions 40×40×160 mm were produced, with various mixes where we changed the amount of replaced sand with crumb rubber and water-cement ratios. These samples were tested for strength in flexure and compression, simultaneously producing force-deflection curves indicating that the rubber granules prevent brittle failure. By full sand replacement, a lightweight cementitious composite was obtained, with the potential for use as acoustic absorption materials and shock energy absorbing layers, but careful consideration of the specific application and mix design is necessary to ensure optimal performance and sustainability. Replacing sand entirely resulted in a lightweight cementitious composite, with densities of 2222 kg/m3 for 10 % replacement and 1525 kg/m3 for 100 % replacement by volume. This material holds promise for applications in acoustic absorption and shock energy absorption. However, achieving optimal performance and sustainability requires thoughtful consideration of the specific application and mix design.